2015
DOI: 10.1158/1940-6207.capr-14-0424
|View full text |Cite
|
Sign up to set email alerts
|

Selecting High-Risk Individuals for Lung Cancer Screening: A Prospective Evaluation of Existing Risk Models and Eligibility Criteria in the German EPIC Cohort

Abstract: Lung cancer risk prediction models are considered more accurate than the eligibility criteria based on age and smoking in identification of high-risk individuals for screening. We externally validated four lung cancer risk prediction models (Bach, Spitz, LLP, and PLCO M2012 ) among 20,700 ever smokers in the EPIC-Germany cohort. High-risk subjects were identified using the eligibility criteria applied in clinical trials (NELSON/ LUSI, DLCST, ITALUNG, DANTE, and NLST) and the four risk prediction models. Sensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 39 publications
0
66
0
Order By: Relevance
“…Previous studies have also compared the performance of different lung cancer risk prediction models [20,21]. D’Amelio et al examined the discriminatory performance of three risk prediction models for lung cancer incidence in a case–control study and found modest differences between the models [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also compared the performance of different lung cancer risk prediction models [20,21]. D’Amelio et al examined the discriminatory performance of three risk prediction models for lung cancer incidence in a case–control study and found modest differences between the models [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study considered a limited number of participants (1,066 cases and 677 controls) and did not consider other aspects of model performance such as calibration or clinical usefulness. Li et al examined four risk prediction models for lung cancer incidence in German participants of the European Prospective Investigation into Cancer and Nutrition cohort [21]. They found that while the differences between most of the evaluated models were modest, generally only the Bach and the PLCOm2012 models had similar or better sensitivity and specificity compared to the eligibility criteria used in the NLST and other eligibility criteria that were used in various European lung cancer screening trials (which applied less restrictive smoking eligibility criteria than the NLST).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LLP model also exhibited modest to good discrimination (AUCs, 0.67–0.82) when assessed alone in several European and U.S. study populations [44]. In more recent and extensive external validation studies, however, the PLCO M2012 model demonstrated the best performance, with respect to discrimination, calibration, sensitivity, and specificity, although not exceedingly better than the Bach model [45, 46]. In support, a study of >95,000 Australian smokers aged ≥45 years also found that the PLCO M2012 model displayed good calibration and discrimination (AUC, 0.80), and that its performance was largely driven by the main predictors of the Bach model, age and smoking history [47].…”
Section: Predicting Lung Cancer Risk Prior To Screening Initiationmentioning
confidence: 99%
“…As in the NLST, the eligibility criteria for the European trials were based on age and a simplified index of past cumulative smoking exposure, plus time since quitting for former smokers. The criteria, however, differed from those in the NLST in terms of specific age range, minimum lifetime smoking duration, cumulative smoking exposure (pack years), and maximum time since smoking cessation (7,8) and the criteria varied also across the European trials themselves.…”
mentioning
confidence: 99%